Pengambilan pil ferus dan faktor-faktor yang berkaitan dalam kalangan ibu mengandung di Johor Bahru - Siti Khatijah AR,; Rosnah S, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2009)
Background : Anemia in pregnancy is a worldwide problem. Ministry of Health Malaysia has conducted prophylaxis program to distribute hematinic pills to pregnant women since 3 decades ago. Methodology : A cross sectional study was conducted among pregnant women who attended government health clinics in Johor Bahru district to assess the prevalence of taking iron tablet and factors associated with it by using a structured questionnaire. Result : Prevalence of respondents taking ferrous pill daily was 68.6%. Anemia prevalence found in this study was 37.5%. Majority of the respondents did not take pills regularly said their reason as forgotten(54.0%), side effects caused by taking pill (39.3%) and did not like the taste (6.7%). The haemoglobin mean was directly inclined with frequency of ferrous pill intake. The significant associated factor in taking iron pill was only frequency of drinking tea. Multivariate logistic regression analyses revealed that drinking tea was the only factor that contributing to iron pills consumption. Conclusion : Education is the most important factor in improving adherence to iron pill. Besides that, motivation and behaviour modification of pregnant women also needs to be taken into account.